Oxidation of Fe(II) leads to increased C‐2 methylation of pentacyclic triterpenoids in the anoxygenic phototrophic bacterium Rhodopseudomonas palustris strain TIE‐1. Issue 3 (9th March 2013) - Eickhoff, M.; Birgel, D.; Talbot, H. M.; Peckmann, J.; Kappler, A.
Abstract Hopanoids are among the most widespread biomarkers of bacteria that are used as indicators for past and present bacterial activity. Our understanding of the production, function, and distribution of hopanoids in bacteria has improved greatly, partly due to genetic, culture‐independent studies. Culture‐based studies are important to determine hopanoid function and the environmental conditions under which these compounds are produced. This study compares the lipid inventory of Rhodopseudomonas palustris strain TIE‐1 under anoxic photoautotrophic conditions using either H2 or Fe(II) as electron donor. The high amount to which adenosylhopane is produced irrespective of the used electron donor suggests a specific function of this compound rather than its exclusive role as an intermediate in bacteriohopanepolyol biosynthesis. C‐2 methylated hopanoids and tetrahymanol account for as much as 59% of the respective C‐2 methylated/non‐methylated homologs during growth with Fe(II) as electron donor, as compared with 24% C‐2 methylation for growth with H2. This observation reveals that C‐2 methylated hopanoids have a specific function and are preferentially synthesized in response to elevated Fe(II) concentrations. The presence of C‐2 methylated pentacyclic triterpenoids has commonly been used as a biosignature for the interpretation of paleoenvironments. These new findings suggest that increased C‐2 methylation may indicate anoxic ferrous conditions, in addition to other environmental stressors that have been previously reported.